THE IMPACT OF COGNITIVE STYLES ON ACADEMIC SUCCESS: AN ANALYSIS OF KURDISH EFL LEARNERS’ ACADEMIC ACHIEVEMENT - AHMED, SAGVAN MOHAMMED ALI (Journal of Duhok University, 2023)
The purpose of this research is to determine how field-independent and field-dependent cognitive styles relate to one another, as defined by Herman Witkin’s Field Dependence-Field Independence theory, and the academic progression of Kurdish EFL learners at the College of Languages, University of Duhok. Utilizing the Group Embedded Figure Test (GEFT) as the primary research instrument, insights from a cohort of 49 participants across sophomore, junior, and senior years were extracted. Findings reveal a significant correlation between cognitive styles and the academic progression of the learners. There’s also a marked gender difference, with females predominantly showcasing field-independent tendencies and males leaning towards field dependence. These findings emphasize the critical significance of educators’ ability to acknowledge and tailor their instructional approaches to accommodate diverse cognitive orientations, which can significantly influence learning strategies, academic outcomes, and the overall educational experience.